Pendidikan Sepanjang Hayat dalam Perspektif Al-Qur’an dan Hadits - Lestari, Sriwiji; Qomaria, Uchik Rini; Adawiyah, Robiatul; Abdurrahman, Abdurrahman (MOMENTUM : Jurnal Sosial dan Keagamaan, 2025)
Lifelong education is a fundamental concept in Islam, rooted in both the Qur’an and the Hadith. Islam regards the pursuit of knowledge as a lifelong obligation for every believer. This study aims to analyze the meaning of lifelong learning in Islamic teachings and its relevance to modern educational frameworks. Using a qualitative literature review approach, this research explores key Qur’anic verses such as Al-‘Alaq:1–5, Ṭāhā:114, and Al-Mujādilah:11, along with prophetic traditions emphasizing continuous learning. The findings reveal that Islam promotes ongoing self-development encompassing spiritual, intellectual, moral, and social dimensions. This aligns closely with UNESCO’s lifelong learning paradigm. Thus, lifelong education in Islam is not only a modern necessity but also an inherent principle of Islamic doctrine guiding humans toward holistic excellence (insān kāmil).